Diversity and Antibiotic Susceptibility of Acinetobacter Strains From Milk Powder Produced in Germany - Cho, Gyu-Sung; Li, Bo; Rostalsky, André; Fiedler, Gregor; Rösch, Niels; Igbinosa, Etinosa; Kabisch, Jan; Bockelmann, Wilhelm; Hammer, Philipp; Huys, Geert; Franz, Charles M. A. P. (Frontiers in Microbiology, 2018)
Forty seven Acinetobacter spp. isolates from milk powder obtained from a powdered milk producer in Germany were investigated for their antibiotic resistance susceptibilities, in order to assess whether strains from food harbor multiple antibiotic resistances and whether the food route is important for dissemination of resistance genes. The strains were identified by 16S rRNA and rpoB gene sequencing, as well as by whole genome sequencing of selected isolates and their in silico DNA-DNA hybridization. Furthermore, they were genotyped by rep-PCR together with reference strains of pan-European groups I, II and III strains of Acinetobacter baumannii. Of the 47 strains, 42 were identified as A. baumannii, 4 as A. pittii and one as A. calcoaceticus based on 16S rRNA gene sequencing. In silico DNA-DNA hybridization with the genome sequence data of selected strains and rpoB gene sequencing data suggested that the 5 non-A. baumannii strains all belonged to A. pittii, suggesting that the rpoB gene is more reliable than the 16S rRNA gene for species level identification in this genus. Rep-PCR genotyping of the A. baumannii strains showed that these could be grouped into four groups, and that some strains clustered together with reference strains of pan-European clinical group II and III strains. All strains in this study were intrinsically resistant towards chloramphenicol and oxacillin, but susceptible towards tetracycline, tobramycin, erythromycin and ciprofloxacin. For cefotaxime, 43 strains (91.5%) were intermediate and 3 strains (6.4%) resistant, while 3 (6.4%) and 21 (44.7%) strains exhibited resistance to cefepime and streptomycin, respectively. Forty six (97.9%) strains were susceptible to amikacin and ampicillin-sulbactam. Therefore, the strains in this study were generally not resistant to the clinically relevant antibiotics, especially tobramycin, ciprofloxacin, cefepime and meropenem, suggesting that the food route probably poses only a low risk for multidrug resistant Acinetobacter strains or resistance genes.